Learning organizations - Reid, Malva Daniel; Bekbalaeva, Jyldyz; Bedford, Denise; Garcia-Perez, Alexeis; Jones, Dwane (Working methods for knowledge management, 2021)
The 21st century economy is fuelled by knowledge. Today, knowledge is more than an idea - it is an economic commodity. An organization's knowledge capital is a competitive and comparative advantage. Every organization must now invest in the knowledge assets of all its employees. Learning is the engine that creates and renews knowledge capital. Learning Organizations delves into why learning is an essential business operation; how modern learning is different from industrial-era training; how to discover learning sources and opportunities; how to design a learning environment and learning strategies that optimize the potential of every employee. This is essential reading for business managers, human resource professionals, and academic researchers studying knowledge economies, knowledge, and intellectual capital.